1999
DOI: 10.1111/1469-7610.00464
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Age and Educational and Psychosocial Outcomes in Early Adulthood

Abstract: The relationships between maternal age (at birth) and educational and psychosocial outcomes at age 18 were examined in a birth cohort of 1025 New Zealand children. This analysis indicated the presence of consistent tendencies for increasing maternal age to be associated with declining risks of educational underachievement, juvenile crime, substance misuse, and mental health problems. Children with teenage mothers had risks of later adverse outcomes that were 1n5 to 8n9 times higher than the risks for offspring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
131
3
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 206 publications
(153 citation statements)
references
References 36 publications
(52 reference statements)
14
131
3
1
Order By: Relevance
“…Our finding that mother’s education is associated with offspring externalising problems is in agreement with findings from previous studies [45, 47]. The lack of association with internalising problems was contrary to previous studies that had demonstrated associations of parental education (not necessarily the mother’s) with internalizing problems in adolescents [45, 48, 49].…”
Section: Discussionsupporting
confidence: 89%
“…Our finding that mother’s education is associated with offspring externalising problems is in agreement with findings from previous studies [45, 47]. The lack of association with internalising problems was contrary to previous studies that had demonstrated associations of parental education (not necessarily the mother’s) with internalizing problems in adolescents [45, 48, 49].…”
Section: Discussionsupporting
confidence: 89%
“…The 5-year-old children of young mothers were disadvantaged by four childhood problems which longitudinal research has shown to be strong predictors of poor outcomes when children reach adulthood: poor infant health (Wadsworth, 1999), abusive harm (Widom, 1989), low IQ (Lubinski, 2000, and problem behaviours (Farrington, 1995). The findings of this and other studies suggest that difficulties indexed by early motherhood have a long reach, and will continue to reverberate into the next generation (Fergusson & Woodward, 1999;Furstenberg, Levine, & Brooks-Gunn, 1990;.…”
Section: The Long Reach Of Adversitymentioning
confidence: 55%
“…This “thrifty” phenotype alone might explain the increased risk of adult adiposity and hypertension in the offspring of older mothers although it should be noted that if these are effects of the intrauterine environment, those effects do not appear to be mediated by the offspring’s birth weight or birth length (Supplementary Table S16). Additionally, however, people tend to gain in wealth and experience as they age, meaning that older parents potentially provide a more resource-rich environment for their offspring5360. Such an environment could counteract the lower birth weight and length of children born to older parents to produce heavier and more hypertensive adults.…”
Section: Discussionmentioning
confidence: 99%